A computational study of the interaction of the foot and mouth disease virus VP1 with monoclonal antibodies - Marrero Diaz De Villegas, Rubén; Rodríguez Limardo, Ramiro; Carrillo, Elisa Cristina; Konig, Guido Alberto; Turjanski, Adrián G. (Elsevier, 2019)
Foot and mouth disease is caused by a non-enveloped virus (FMDV), which disposes several antigenic sites at the surface of their capsid proteins. The most relevant and immunodominant antigenic site of FMDV (site A or AnSA) includes a key virus–cell interaction element (RGD motif) located in the Viral Protein 1 (VP1), more precisely at the GH loop. AnSA includes a set of overlapped and mainly linear epitopes, which are the main targets of the humoral immune response. Taking advantage over specific structural features of the GH loop, we have evaluated the influence of every amino acid residue at AnSA in the interaction with 2 neutralizing antibodies by molecular modeling techniques. Additionally, we constructed diverse interaction complexes with multiple site A mutants and discussed about the structural influence of amino acidic insertions in such relevant antigenic site of FMDV. Our approach is in agreement with previous ELISA experiments and allows the understanding of how FMDV mutations may alter the interaction with different antibodies, as we can estimate the contribution of each amino acid to the interaction. Overall, our work contributes to the development of specific vaccination strategies for FMD control.